2009
DOI: 10.1007/s00198-009-1110-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alendronate on bone metabolic indices and bone mineral density in patients treated with high-dose glucocorticoid: a prospective study

Abstract: Alendronate was effective in suppressing bone resorption and subsequent BMD decrease at the lumbar spine in patients with high-dose GC treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 33 publications
1
4
0
1
Order By: Relevance
“…In our study, there was no significant change in the serum level of BAP after glucocorticoid therapy, and previous studies (18)(19)(20) have also found no significant change in the serum BAP level with glucocorticoid therapy. In fact, BAP may not be directly regulated by glucocorticoids because the glucocorticoid response element is not present in the promoter region of the BAP gene (29).…”
Section: Discussionsupporting
confidence: 70%
“…In our study, there was no significant change in the serum level of BAP after glucocorticoid therapy, and previous studies (18)(19)(20) have also found no significant change in the serum BAP level with glucocorticoid therapy. In fact, BAP may not be directly regulated by glucocorticoids because the glucocorticoid response element is not present in the promoter region of the BAP gene (29).…”
Section: Discussionsupporting
confidence: 70%
“…The notion that bone resorption is tightly linked to glucose homeostasis is clinically important, since most of the drugs used in the treatment of bone disease patients target this aspect of bone remodeling. Specifically, high levels of fasting plasma glucose are measured in osteoporotic women treated with bone resorption inhibitory drugs, and there is a significant and positive correlation between undercarboxylated Ocn and urinary cross-linked N-telopeptides of type I collagen (NTX) [54,55].…”
Section: Glucose Metabolismmentioning
confidence: 99%
“…Such agents have been shown to promote vascular injuries and endothelial damage ( 17 ); however, their role in the pathogenic process of the disease has not been precisely clarified. In the current patient, we believe that the significant increase in the urinary level of NTx should mirror the concomitant disturbance of the bone and calcium metabolism which was induced by the systemic administration of glucocorticoid ( 19 ). Although the patient was no longer dependent on HD at the onset of calciphylaxis, the temporal decline in his renal function might also have predisposed him to the disease through the concurrent mineral disturbance characterized by hyperphosphatemia, which encouraged us to use calcium carbonate as a phosphate binder.…”
Section: Discussionmentioning
confidence: 81%